EFIKASI DIRI DAN PERILAKU INOVATIF: PERAN DUKUNGAN ORGANISASI - Noerchoidah Noerchoidah; Tri Ariprabowo; Nurdina Nurdina (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study aims to analyse the impact of self-efficacy on innovative behaviour and the moderating role of organisational support on self-efficacy and innovative behaviour. This study uses an explanatory research type. The respondents of this study were 149 lecturers at private universities in Surabaya. Data is collected using a questionnaire via a google form. Sampling using a purposive sampling technique. Data analysis using Partial Least Square (PLS) software. The results showed that self-efficacy had a positive and significant effect on the innovative behaviour of lecturers. Direct organisational support has a positive and insignificant effect on innovative behaviour. However, organisational support strengthens self-efficacy toward the innovative behaviour of private university lecturers in Surabaya. The study results follow the theory of social exchange. This research implies that faculty support given to lecturers will make them improve their self-efficacy and strengthen their innovative behaviour to produce their best performance.